ChemInform Abstract: The Synthesis of Tetrazoles in Nanometer Aqueous Micelles at Room Temperature. Issue 42 (14th October 2014) - Xie, Aming; Cao, Meiping; Liu, Yangyang; Feng, Liandong; Hu, Xinyu; Dong, Wei
Abstract A newly developed nonionic amphiphile acts as an effective nanomicelle‐forming species for the synthesis of tetrazoles by 1, 3‐dipolar cycloadditions under aqueous conditions.